PREDICTION AND OPTIMIZATION ANALYSIS OF DURABILITY PERFORMANCE OF AUTOMOTIVE CLOSURES - GUO PengBo; LIU Zhe; LI Hui; GAO DaWei (Jixie qiangdu)
Aiming at the fatigue failure problem of a car door opening and closing process.The Hypermesh was used to construct a finite element model of door opening and closing,and then Ls⁃Dyna,an explicit dynamics solver,was used to establish a nonlinear transient dynamics model of door opening and closing.The d3plot file containing the stress⁃time history solved by the nonlinear transient analysis was imported into nCode DesignLife to build the fatigue analysis module,and the results were verified with 100000 times of door opening and closing durability tests,and the conclusions show that both of them have good consistency in terms of the damage location and the damage degree.Finally,multi⁃particle swarm optimization(MPSO)was used to optimize the door with the objectives of door lightweight and minimum damage,and the optimal solution was selected according to the engineering reality,which reduced the mass of the door assembly by 0.17 kg,and the damage value of the door was reduced by about 24.33%.The optimization results show that the MPSO algorithm can be effectively applied to the multi⁃objective optimization design of the door,which provides certain ideas for the design and development of the subsequent door.